Banking Regulation and Financial Soundness Nexus in View of the Crisis: An Islamic Banking Perspective - Daoud, Yomna; Kammoun, Aida (International Journal of Economics and Financial Issues, 2024)
The COVID-19 pandemic significantly affected global finances and economies, posing a risk of global GDP decline. This research examines the soundness and dynamics of Islamic banks from 2017Q1 to 2023Q1. The study focuses on eight countries selected based on the systemic importance of their Islamic banks: Saudi Arabia, UAE, Bahrain, Oman, Pakistan, Malaysia, Brunei, and Indonesia. The analysis is based on several key indicators including size, profitability, non-performing financing, and capital adequacy. Our analysis shows that the Islamic banks' response to the pandemic is not uniform across jurisdictions. Saudi Arabia and Southeast Asian countries (Malaysia and Indonesia) are expected to remain stable. This reflects the Islamic banks' desire to integrate more closely into the global financial system by holding higher capital adequacy ratios. Effective banking regulation is necessary to ensure the stability and credibility of the financial industry. Other regions may face challenges that require additional policies to ensure the stability of their Islamic banking sectors. Several financial soundness indicators and jurisdictions have shown notable improvements, with some levels reaching pre-pandemic levels. This reflects the effectiveness of the COVID-19 policy support measures implemented since 2020.